2022
DOI: 10.3389/fneur.2022.926320
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Pre-operative BUN and Post-operative 30-Day Mortality in Patients Undergoing Craniotomy for Tumors: Data From the ACS NSQIP Database

Abstract: ObjectiveThere is limited evidence to clarify the specific relationship between pre-operative blood urea nitrogen (BUN) and post-operative 30-day mortality in patients undergoing craniotomy for tumors. Therefore, we aimed to investigate this relationship in detail.MethodsElectronic medical records of 18,642 patients undergoing craniotomy for tumors in the ACS NSQIP from 2012 to 2015 were subjected to secondary retrospective analysis. The principal exposure was pre-operative BUN. Outcome measures were post-oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…BUN is a low-molecular-weight nitrogen product derived from protein catabolism and excreted by the kidney [ 24 ]. Therefore, BUN reflects protein intake, endogenous protein catabolism, fluid balance, hepatic urea synthesis, and fluid/renal status in critically ill patients and have been widely used as a prognostic marker in patients with various surgical diseases [ 5 , 7 , 25 ]. Similarly, albumin also has various biological effects, including maintenance of osmotic pressure, binding and transport of various drugs, and neutralization of free radicals, and hypoalbuminemia has been identified as a poor prognostic factor in critically ill surgical patients [ 9 , 11 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…BUN is a low-molecular-weight nitrogen product derived from protein catabolism and excreted by the kidney [ 24 ]. Therefore, BUN reflects protein intake, endogenous protein catabolism, fluid balance, hepatic urea synthesis, and fluid/renal status in critically ill patients and have been widely used as a prognostic marker in patients with various surgical diseases [ 5 , 7 , 25 ]. Similarly, albumin also has various biological effects, including maintenance of osmotic pressure, binding and transport of various drugs, and neutralization of free radicals, and hypoalbuminemia has been identified as a poor prognostic factor in critically ill surgical patients [ 9 , 11 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…17 day mortality in patients who underwent craniotomy for tumors. 18 The proper preoperative management of BUN and the maintenance of BUN near the inflection point (9.804 mg/dL) could reduce the risk of postoperative 30day mortality.…”
Section: Unplanned 30-day Readmissionmentioning
confidence: 99%
“…Elevated BUN levels reflect the function of many body systems and are associated with poor kidney function, dehydration, acute hemodynamic alterations, and acute neurohumoral alterations [7,18]. Therefore, high BUN has been correlated with increased mortality in many patient populations, including those with heart failure, acute myocardial infarction, pneumonia, exacerbation of chronic obstructive pulmonary disease, and after cranial tumor resection and surgical resection for pancreatic adenocarcinoma [19][20][21][22][23]. Often, elevated BUN is associated with elevations in creatinine, but Beier et al reported that high BUN levels were correlated with increased short-term and long-term mortality after ICU admission, independent of creatinine levels [24].…”
Section: Introductionmentioning
confidence: 99%